Process-based model in adolescence: analyzing police legitimacy and juvenile delinquency within a legal socialization framework - Baz, Olalla (European journal on criminal policy and research, 2018)
The empirical evidence on the process-based model of self-regulation shows that procedural justice evaluations and the perceived legitimacy of authorities impact law-abiding behavior. However, few studies analyze this theory from the perspective of adolescent legal socialization. The present study aims to examine the process-based model and other socializing agents such as family, school and peers that may have an effect on it. The sample comprised 2041 youths residing in Spain, aged between 13 and 18 years. The data form part of the Third International Self-Report Delinquency Study (ISRD-3). Multiple linear regression analyses were conducted to predict police legitimacy and juvenile delinquency. The results reveal that police legitimacy perceptions are not only influenced by procedural justice, but also by parental monitoring, school attachment, and delinquent peers. Moreover, perceptions of police legitimacy, parental monitoring, and delinquent peers predict juvenile delinquency. These findings complement and add new explanatory factors to the process-based model.